Comparative Analysis of the Major Points Under FAS Revenue, RAS 2/2008 Accounting for Construction Contracts, IFRS 15 Revenue on Contracts with Buyers and Recommendations for Refine the Draft Standard - N. S. Suleymanov (Учёт. Анализ. Аудит, 2024)
The paper is relevant because it addresses the absence of regulatory documents for determining work completion and accounting revenue recognition in non-construction industries. The study aimed to analyze the innovations of the draft FAS Revenue in accounting, specifically regarding revenue and income recognition. It also aimed to identify major discrepancies with the currently applicable IFRS 15 Revenue on Contracts with Buyers and RAS 2/2008 Accounting for Construction Contracts. Also, the work endeavours developing recommendations for refine the draft FAS Revenue on revenue recognition and determining the completion level of work when performing research and development (R&D) under long-term contracts. The author considers new concepts and definitions of the draft standard, considering their probable practical application in modern conditions. The author presents a rationale for the need for priority application of the expert method for assessing the level of completion of R & D under long-term contracts. Based on the principle of rationality and materiality, the author formulates the criteria for recognizing contracts as long-term. Also, the research gives some advice for improving theoretical and organizational-methodological points for accounting of revenue under long-term contracts, ensuring more complete and reliable presentation of accounting (financial) statements. This work’s results can help organizations enhance the quality and reliability of their accounting statements. More over, it can help reduce labor costs associated with preparing these statements using the revenue recognition method. The study used analysis methods, comparison, grouping, the method of analogies, the method of comparison and generalization of regulatory sources and scientific literature on the topic of the study.